Contribuição ao estudo do comportamento de concretos produzidos com resíduo do beneficiamento de rochas ornamentais tratado termicamente em relação aos aspectos mecânicos e de durabilidade. - Mittri, Sérgio Hémerson de Moraes (2016)
Brazil is a significant producer of ornamental stones, having Espírito Santo as the main producing state. In the stone beneficiation process about 30% of the total volume of the block becomes waste. Many studies have used this waste in cementitious matrices, using it as a material capable of partially fill the pores of the cement matrix (filler effect). However, these studies have been conducted for two decades and until now the construction industry did not absorb the ornamental stone waste, which remains an environmental liability. To improve the properties of this material, this study treated it thermally at 1200°C. The ornamental stone west after thermal treatment (OSWTT) was subjected to various characterization tests, including tests to determine the pozzolanic activity according to NBR 12653 (ABNT, 2015). Concrete were made with 0%, 5% and 10% addition of OSWTT with the objective of evaluating the influence of this addition on the mechanical strength of concrete and also to evaluate the durability of them, with a focus on penetration of chloride ions. In relation to the pozzolanicity, the results showed that the OSWTT met all the criteria required by the standard, then it is considered a pozzolanic material. Furthermore, the concretes produced with the addition of OSWTT showed a significant increase in compressive strength. Concerning the penetration of chloride ions, the concrete with OSWTT addition showed greater resistance when compared to the reference concrete.